ANALYSIS OF CODE SWITCHING BY EFL STUDENT AT ENGLISH LANGUAGE EDUCATION - Ni Putu Trisna, Sariputri (Universitas Pendidikan Ganesha, 2017)
This study discusses code switching used by the English Language Education students in their daily communication. This study also tries to find out the factor of applying code switching. The data was collected from around forty participants by using two methods such as observation and interview. The participants were the English Language Education students at Universitas Pendidikan Ganesha. From all of the participants, there were twenty expressions of code switching were revealed. The result shows that the students uses three types of linguistics level in code swicthing such as word level, phrase level and clause or sentence level. It is also found that there are two factors that made the students switch the one language into another language.